The Impact of Sugar-Sweetened Beverages on Type 2 Diabetes Mellitus: A Scoping Review - Tri Siswati; Fifi Novianti Puspita Sari; Hanifah Salsabila; Almira Sitasari; Agus Wijanarka; Nugraheni Tri Lestari (Ficco Scientific Corner, 2025)
Background: The increasing consumption of sugar-sweetened beverages (SSBs) has become a major public health concern due to its link with metabolic diseases, particularly Type 2 Diabetes Mellitus (T2DM). Understanding the relationship between SSB consumption and the risk and progression of T2DM, particularly in adult populations, is crucial for developing targeted interventions. This scoping review aims to summarize observational studies that investigate the association between SSB consumption and T2DM risk and progression in adult populations. Methods: This scoping review included nine studies published between 2017 and 2023. The inclusion criteria were studies that involved adult populations (≥18 years) and explored the relationship between SSB consumption and T2DM. Databases such as PubMed and Google Scholar were searched using keywords like ‘sugar-sweetened beverages,’ ‘type 2 diabetes,’ and ‘adult,’ and ‘progression.’ Results: The studies reviewed consistently showed a positive association between frequent SSB consumption and the risk of developing T2DM. Overall, the evidence supports that SSBs contribute significantly to the incidence and progression of T2DM, often through weight gain and increased insulin resistance. Conclusion: This review shows the strong association between SSBs and T2DM, urgent public health interventions are needed to regulate consumption, particularly among high-risk groups. Future research was needed to examine the long-term impact of SSB on diabetes.